Marigold's missing magpie - Falconer, Keith R.; Madder, Sharyn (Macmillan Education Australia South Yarra, Vic., 1998)
Marigold's Missing Magpie by Keith R. Falconer is an engaging children's book that follows the story of Marigold, a young girl who loves her pet magpie. One day, her beloved bird goes missing, prompting Marigold to embark on an adventurous quest to find her feathered friend. Along the way, she encounters various characters and learns important lessons about perseverance, friendship, and the significance of caring for animals. With a blend of mystery and heartwarming moments, the story captures the excitement of the search and the bond between Marigold and her magpie. Richly illustrated and filled with charming dialogue, this tale inspires young readers to value their connections with pets and the importance of empathy.